2019
DOI: 10.1177/1474022219871001
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative investigation of stress related to studying architecture at degree level in the UK

Abstract: Architecture students have been reported to experience significant stress, yet little has been researched. This study aims to examine how architecture students experience and cope with stress. Twelve participants studying Architecture at bachelors and masters levels took part in individual interviews. Interviews were transcribed verbatim and analysed using thematic analysis. Three over-arching themes emerged: sources of stress in architecture studies, effects of stress and coping with stress. Participants repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Additionally, sometimes, they encounter several difficulties when responding to instructors’ criticism and correction. According to Xie et al (2019) and Rauf et al (2020), critique of tutor’s is important source of stress for architecture students. Furthermore, some students behave recklessly when the tutors critique them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, sometimes, they encounter several difficulties when responding to instructors’ criticism and correction. According to Xie et al (2019) and Rauf et al (2020), critique of tutor’s is important source of stress for architecture students. Furthermore, some students behave recklessly when the tutors critique them.…”
Section: Discussionmentioning
confidence: 99%
“…Hegenauer (2018) emphasised OHI 46,2 that the huge number of projects and exams can lead to sense of oppression among many students because of the time required to accomplish the heavy workload. Xie et al (2019) reported that heavy workloads and culture of working hard are the main sources of stress for architecture students. The findings of these three studies that were conducted among architecture students support the results of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental well-being extends beyond the absence of mental health conditions to enable individuals to realise personal potential, be resilient amidst adversities, function productively, form meaningful relationships, and contribute to respective communities (World Health Organisation, n.d.). The demanding nature of design courses and the intensely individualistic competitive learning environment created significant stress for design students (AIAS, 2008;Gümüşburun Ayalp & Çivici, 2021;Hegenauer, 2018;Howlett Brown, 2022;Jia et al, 2009;Karklins & Mendoza, 2016;Kirkpatrick, 2018;Leon et al, 2014;McClean, 2020;Olweny et al, 2021;RIBA, 2017RIBA, , 2018SONA, 2022;Stead et al, 2022;Xie et al, 2019) and negatively impacted student mental well-being since the 1960s (Braaten, 1964) as the main detriment (Kirkpatrick, 2018). Furthermore, design criticisms that emerge toward beginning design students might be unconsciously internalised as intimidating acts, which produce negative emotions of failure and incompetence.…”
Section: Detriments Of the Master-apprentice Pedagogymentioning
confidence: 99%